2019
DOI: 10.1002/pen.25249
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of EPDM and FPM elastomers irradiated at very high dose rates in mixed gamma and neutron fields

Abstract: Elastomers are widely used in radioactive environments, where ionizing radiations induce a deterioration of their properties due to degradative phenomena occurring in the polymer structure. Their radiation resistance is usually assessed using γ‐rays and relatively low dose rates, but in actual applications, they are often exposed to mixed radiation fields and higher dose rates. Ethylene propylene diene monomer (EPDM) is known for its excellent resistance to γ‐rays but absorbs a larger dose by neutron interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The mechanical properties of these studied samples are tightly related to the level of γ-irradiation [43], whose values are the combination between this scission process and a certain degree of crosslinking [65]. The illustration of this overlapping is based on the extended durability that occurs in nuclear power plants [40,66].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…The mechanical properties of these studied samples are tightly related to the level of γ-irradiation [43], whose values are the combination between this scission process and a certain degree of crosslinking [65]. The illustration of this overlapping is based on the extended durability that occurs in nuclear power plants [40,66].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…EPDM is usually synthesized by solution polymerization technique in a continuous process. Several additives in the form of antioxidants [14], vulcanizing agents [15], accelerators [16], reinforcing agents [17], activators [18], and processing aids [19] are also mixed to improve its inherent properties. To reinforce [20] the EPDM matrix, carbon black or silica are added as ller or grafted by means of entanglement among polymeric chain structure as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…EPDM had the highest irradiation resistance, which depended on the material’s inorganic content. Battini et al [ 14 ] and Ferrari et al [ 15 ] conducted several studies on the degradation of EPDM elastomers irradiated at high dose rates in mixed neutron and gamma fields and found that material degradation was mainly influenced by the total absorbed dose as opposed to the irradiation type and irradiation dosage.…”
Section: Introductionmentioning
confidence: 99%